THE ROLE OF TECHNOLOGY IN THE INDONESIAN ECONOMY: A SYSTEM DYNAMICS MODEL - Tasrif, Muhammad (Journal of S&T Policy and R&D Management, 2014)
It is an accepted view that technological progress is an extremelyimportant, perhaps the most important, determinant in the growth in output per man. Therefore, the governments policies related to the R & D activities to spur the development of the technology in order to enhance economic growth in Indonesia are becoming very important to be analyzed. For this purpose, a process oriented model of technology-economy interactions (Technology-Economy Model) was developed; and through the simulation of the model a clear and distinct understanding of the role of the technology in the Indonesian economy can be obtained. In the model, the capital-labor ratio (KLR) is proposed as an indicator of the technology in an economic system. This implies that the development of technology will be strongly determined by the decisions those related to the development of capital (investment and depreciation) and the growing of labor (hire and fire). The structure of decision making process is naturally consists of the interdependent relationships among some components which constructing causal loops (feedback loops). Based on this thought, the system dynamics methodology is used in this study to develop the Technology-Economy Model. The growth behavior of the technology and the economy is obtained through simulating the model from year 2000 until year 2050 for some scenarios related to the R&D activities and the economic policies. The analysis of the model behavior provides some important policy directions those expected to produce the higher technology and economic growth and also the better performance of the economy, i.e.: policies to manage R&D activities becoming effective, R&D policies should have a linkage with the education and training policies (link and match), have also a linkage with the economic policies (investment, export, and import), and the development of industry (wage policies).